Factor Price Distortions, Resource Allocation, and Growth: A Computable General Equilibrium Analysis - Kwon, Jene K.; Paik, Hoon (The Review of Economics and Statistics, 1995)
Jene K. Kwon, Hoon Paik, Factor Price Distortions, Resource Allocation, and Growth: A Computable General Equilibrium Analysis, The Review of Economics and Statistics, Vol. 77, No. 4 (Nov., 1995), pp. 664-676